Vitamin D3 in acute respiratory infections in patients under age five in a health institution in Colombia (Journal of Medical Science, 2022)
Aim. describe the clinical behavior in acute respiratory infections in patients under age five in a Colombian health institution after VD3 administration. Trial studies are required to determine this potential benefit. Material and Methods. A performed series of 38 patients of both genders, aged 0-60 months to whom 50,000 units of VD3 were orrally administered per month for three months is described. The number of episodes, visits to the emergency room, and hospitalizations due to acute respiratory infections (ARI) before and after VD3 administration were described. Results. The average age of the participants was 25.81 ± 17.50 months. The average number of ARI clinical events per month was 4.02 (95% CI 3.64-4.40) prior to VD3 administration. The number of episodes reduced at the end of the three cycles was 2.23/month (95% CI 1.81-2.65; p = 0.0230). The average number of emergency room visits during three months prior to the VD3 administration was 2.15 (95% CI 1.77-2.53). After three months of treatment, the average number of emergency room visits decreased to 0.52 (95% CI 0.32-0.72; p = 0.0180). Prior to VD3 administration, 31.58% required hospitalization. After the administration of three VD3 doses, only one patient required hospitalization (2.63%; x̄:0.026 (95% CI 0.02-0.03; p = 0.0368). Conclusions. Vitamin D3 administration could have a benefit in reducing the number of ARI episodes, emergency room visits, and hospitalalizations in children under age five.